MICROWAVE SIGNATURE OF POLAR FIRN AND SEA ICE IN THE ANTARCTIC FROM AIRBORNE OBSERVATION - ヤマノウチ, タカシ; ワダ, マコト; YAMANOUCHI, Takashi; WADA, Makoto (National Institute of Polar Research, 1992)
P(論文) Airborne observations of 19.35 GHz microwave radiation were taken over the sea ice and firn cover of Antarctic ice sheet. Microwave brightness temperature was analyzed to explain satellite observations.As for the polar firn over the ice sheet, brightness temperature varied greatly from the coast to the interior, which noticeably corresponded to the mean annual accumulation obtained at the surface. Also found was the variation of brightness temperature on a small scale of about 1-10 km, which became extreme in the sastrugi/glazed surface zone (Z route), where the accumulation is variable. Calculated emissivity using the semi-empirical relation to the accumulation rate and physical temperature proposed in the past could not always explain the observed emissivity because of the limit of the theoretical relation, or shortage of measurements. Satellite passive microwave observations were of very low resolution, making it difficult to show these small scale great variations corresponding to the surface accumulation. In the sea ice area, the brightness temperatures observed were similar to the results from the satellite. Brightness temperature was low for multi-year ice and high for first year fast ice; the brightness temperature for new ice increases from a lower value and converges to the value of first year ice. From the flight across Riiser-Larsen Peninsula, smooth variation up to 225K was seen over the central part of the peninsula. This high value could be explained by the extremely high accumulation, which occurred asymmetrically against the height of the peninsula. Also along the flight, it was easy to distinguish the ice shelf and sea ice, even when covered with snow, by microwave brightness temperature measurement. departmental bulletin paper